2011
DOI: 10.3892/or.2011.1351
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of biomarkers related to tumor initiation and promotion in mouse skin by a natural β-glucuronidase inhibitor and its precursors

Abstract: Carcinogen-mediated labilization of lysosomal enzymes such as β-glucuronidase (βG) is often associated with the general process of inflammation. Therefore, the primary goal of this study was to demonstrate that exposing the skin of SENCAR mice to the natural βG inhibitor D-glucaro-1,4-lactone (1,4-GL) and its precursor D-glucuronic acid-γ-lactone (GUL), prior to and during 7,12-dimethylbenz[α]anthracene (DMBA) treatment inhibits not only epidermal hyperplasia but also inflammation in the mouse skin complete ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…In another study, D-SAL was more therapeutically efficient compared to its natural precursor (D-GL), for reducing epidermal hyperplasia (lethargic tumour promoter) and inflammation in 7,12dimethylbenz(a)anthracene (DMBA)-induced complete skin carcinogenesis of SENCAR mice [125]. Pre and cotreatment of murine models with D-SAL for 4-weeks (twice weekly) by topical administration (0.5e4 mg) or dietary treatment (0.5 and 1%), both significantly reduced epidermal hyperplasia and inflammation by up to 57% of DMBA-controls in a dose-dependent manner.…”
Section: Natural Acids and Lactonesmentioning
confidence: 99%
“…In another study, D-SAL was more therapeutically efficient compared to its natural precursor (D-GL), for reducing epidermal hyperplasia (lethargic tumour promoter) and inflammation in 7,12dimethylbenz(a)anthracene (DMBA)-induced complete skin carcinogenesis of SENCAR mice [125]. Pre and cotreatment of murine models with D-SAL for 4-weeks (twice weekly) by topical administration (0.5e4 mg) or dietary treatment (0.5 and 1%), both significantly reduced epidermal hyperplasia and inflammation by up to 57% of DMBA-controls in a dose-dependent manner.…”
Section: Natural Acids and Lactonesmentioning
confidence: 99%
“…As demonstrated in another study, the topical administration of the βG inhibitor, D-glucaro-1,4-lactone (1,4-GL), or D-glucuronic acid-γ-lactone (GUL) its precursor, to SENCAR mice with skin carcinogenesis, epidermal hyperplasia was significantly reduced along with a decrease in inflammation ( 107 ). Moreover, Ha-ras mutations were reduced upon experimental therapy.…”
Section: Testing Avenues Using Animal Models Of Skin Carcinogenesimentioning
confidence: 83%
“…Moreover, Ha-ras mutations were reduced upon experimental therapy. That study demonstrated that whether administered topically or through diet, therapy with GUL or 1,4-GL was effective in hindering experimental skin tumorigenesis ( 107 ).…”
Section: Testing Avenues Using Animal Models Of Skin Carcinogenesimentioning
confidence: 98%
“…Lysosomale Enzyme wie ß-Glucuronidase (ßG) sind häufig an hyperplastischen epidermalen Prozessen, an der Karzinogenese und Entzündung beteiligt. Es konnte kürzlich gezeigt werden, dass in dem 7,12-dimethylbenz(a)anthrazen induzierbaren Hautkrebsmodell der natürliche Inhibitor G-Glucuro-1,4-Lacton (1,4GL) sowie sein Vorläufermolekül D-Glucuronsäure-gamma-Lacton (GUL) in einer topischen und diätetischen Applikation erhebliche anti-entzündliche und anti-tumoröse Aktivitäten haben [3]. Viele Pflanzeninhaltsstoffe werden an dem Mehrschrittmodell der Haut zur Karzinogenese geprüft.…”
Section: Die Haut Als Organmodell Zum Studium Von Krankheitsbildernunclassified
“…B. die Behandlung von Melasma kaum wissenschaftlich klar strukturiert und standardisiert ist und klinische Studien dringend benötigt werden, um die Wirksamkeit derzeitig marginal effektiver Therapien entscheidend zu verbessern [26]. Störungen in der Melanogenese als klinische Erscheinungsformen von Hautpigmentstörungen sind eng verknüpft mit den Stoffwechselprozessen zur Eumelanin-(dunkel, fotoprotektiv) und zur Phämelanoninbildung (hell, Fotosynthese von Vitamin D [3]); evolutionsbiologisch spielen Glutathion und Melanokortin eine tragende Rolle hinsichtlich der Stimulierung bzw. Inhibition von dunklem und rötlich-hellem Melanin [27].…”
Section: Glutathion Und Bleachingunclassified